Design and PID Control of a Lower Limb Exoskeleton for Virtual Reality-Based Telerehabilitation - Aktan, Mehmet Emin; Falkowski, Piotr; Zawalski, Krzysztof; Jeznach, Kajetan; Omurlu, Vasfi Emre; Akdogan, Erhan (IEEE, 2025)
Rehabilitation is a critical process that enables people who have lost motor skills to regain their physical abilities. Exoskeletons offer innovative solutions to accelerate the functional recovery of patients and increase the effectiveness of treatment. The integration of virtual reality and biological signal processing technologies into such systems allows the user's movements to be detected in real time with high accuracy, enabling remote and personalised treatment. This study explains the working principle and control structure of a 4-degree-of-freedom lower limb exoskeleton robot developed for virtual reality-based telerehabilitation. The details of the electrical components of the system such as controller, input and output units, motor, sensor, virtual reality goggles, EEG and EMG devices and their interrelationships are explained. The position control performance for each joint using the PID control method is analysed. The results show that the exoskeleton can follow the given target trajectories with different error values depending on the period and joint. A maximum position error of 0.659 degrees was observed in the hip flexion-extension joint, while the average error for this joint was recorded as 0.385 degrees.
Keywords: lower limb exoskeleton; PID control; rehabilitation; Engineering; Robotics